Prevalence and diagnosis of bacterial Vaginosis in tertiary care teaching hospital - Dr. Ayesha Farheen; Dr. Aisha Humera (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Bacterial vaginosis is the most common cause of vaginal discharge among women in reproductive age. The normal flora of the vagina varies from person to person, but lactobacilli are usually the preponderant organism. Bacterial flora also contains other aerobic and anaerobic microorganisms. Some of these are considered to be pathogenic. It is recognized that, bacterial vaginosis may be associated with pelvic inflammatory disease, preterm premature rupture of the membranes (PROM), post operative gynaecologic infections and abnormal Papanicolaou smear. Objective: 1) to find the prevalence of bacterial vaginosis. 2). To find the most cost effective reliable method for diagnosis of bacterial vaginosis. Method: A total of 360 consecutive women with complaints of vaginal discharge were considered for the study. The study was undertaken from January 2015 till June 2016 at KBN medical college and hospital, Gulbarga, Karnataka. BV was diagnosed based on Amsel’s composite criteria and Nugent’s scoring system. pH was determined, Whiff amine test for the presence of fishy odor and the presence of the clue cells on vaginal smear were observed. Gram staining was performed for Nugent’s method. Result: Prevalence of BV was 44.16%. Most common affected age group was between 24-35 years. Routinely a combination of various methods are used for the diagnosis of bacterial vaginosis (BV), although nugent criterion is considered as the gold standard method The prevalence rate of BV in present study was high. Conclusion: With limited resources in developing countries, there is a great need for inexpensive diagnostic methods for bacterial vaginosis. Amsel’s criteria is as good as Nugent’s scoring in diagnosis of BV and it is simple, easy, cost effective, fast and reliable, and can be done in OPD which can be used for precise and fast treatment.